The microneme adhesive repeat domain of MIC3 protein determined the site specificity of Eimeria acervulina, Eimeria maxima, and Eimeria mitis - Zhang, Yang; Lu, Mingmin; Zhang, Zhenchao; Huang, Xinmei; Huang, Jingwei; Liu, Jiabin; Huang, Jianmei; Song, Xiaokai; Xu, Lixin; Yan, Ruofeng; Li, Xiangrui (Frontiers in Immunology, 2023)
Understanding the determinants of host and tissue tropisms among parasites of veterinary and medical importance has long posed a substantial challenge. Among the seven species of Eimeria known to parasitize the chicken intestine, a wide variation in tissue tropisms has been observed. Prior research suggested that microneme protein (MIC) composed of microneme adhesive repeat (MAR) domain responsible for initial host cell recognition and attachment likely dictated the tissue tropism of Eimeria parasites. This study aimed to explore the roles of MICs and their associated MARs in conferring site-specific development of E. acervuline, E. maxima, and E. mitis within the host. Immunofluorescence assays revealed that MIC3 of E. acervuline (EaMIC3), MIC3 of E. maxima (EmMIC3), MIC3 of E. mitis (EmiMIC3), MAR3 of EaMIC3 (EaMIC3-MAR3), MAR2 of EmMIC3 (EmMIC3-MAR2), and MAR4 of EmiMIC3 (EmiMIC3-MAR4), exhibited binding capabilities to the specific intestinal tract where these parasites infect. In contrast, the invasion of sporozoites into host intestinal cells could be significantly inhibited by antibodies targeting EaMIC3, EmMIC3, EmiMIC3, EaMIC3-MAR3, EmMIC3-MAR2, and EmiMIC3-MAR4. Substitution experiments involving MAR domains highlighted the crucial roles of EaMIC3-MAR3, EmMIC3-MAR2, and EmiMIC3-MAR4 in governing interactions with host ligands. Furthermore, animal experiments substantiated the significant contribution of EmiMIC3, EmiMIC3-MAR4, and their polyclonal antibodies in conferring protective immunity to Eimeriaaffiliated birds. In summary, EaMIC3, EmMIC3, and EmiMIC3 are the underlying factors behind the diverse tissue tropisms exhibited by E. acervuline, E. maxima, and E. mitis, and EaMIC3-MAR3, EmMIC3-MAR2, and EmiMIC3-MAR4 are the major determinants of MIC-mediated tissue tropism of each parasite. The results illuminated the molecular basis of the modes of action of Eimeria MICs, thereby facilitating an understanding and rationalization of the marked differences in tissue tropisms among E. acervuline, E. maxima, and E. mitis.